KUALITAS PRODUK DAN HARGA SERTA DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN: Studi Kasus pada pengguna Samsung Galaxy S20 Series di Indonesia - Ridwanudin*, Riki; Oktafani, Farah (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
This study was conducted to determine the effect of product quality and price on purchasing decisions for the Samsung Galaxy S20 in Indonesia. The purpose of this study was to determine and analyze how consumer perceptions of product quality, how purchase decisions for the Samsung Galaxy S20, and the magnitude of the influence of product quality and price simultaneously and partially. on the decision to purchase the Samsung Galaxy S20 Series in Indonesia. Based on a simultaneous hypothesis test, product quality and price have a significant effect on purchasing decisions for the Samsung Galaxy S20 Series. Based on the results of partial hypothesis testing (t-test) it was found that product quality and price variables had a significant effect on purchasing decisions for the Samsung Galaxy S20 Series in Indonesia. Based on the coefficient of simultaneous determination that product quality and price can affect purchasing decisions 52.9% and other factors of 47.1% are influenced by other factors not examined in this study. Keywords: Price, Product Quality, Purchase Decision, Marketing Mix, Marketing.